Answer:
X = 9
Step-by-step explanation:
6(x−3)=3x+9
(6)(x)+(6)(−3)=3x+9
6x+−18=3x+9
6x−18=3x+9
6x−18−3x=3x+9−3x
3x−18=9
3x−18+18=9+18
3x=27
3x/3 = 27/3
Answer: 7
Step-by-step explanation:
To find the distance between the two point, we simply use this formular:
D = √ (x₂ -x₁)² + (y₂ - y₁ )²
x₁ = -4 y₁ =3 x₂=-4 y₂ = -4
D = √(-4-[-4])² + (-4-3)²
(-4-[-4])²= (-4+4)²=(0)²=0
(-4-3)² = 49
D = √0+49
D= √49
The square root of 49 is 7
D=7
Therefore the distance between (-4 3) and (-4 -4) is 7
x ≥ 2
x ≥ 8
x ≥ 16
x ≥ 24